Genetic variability and principal component analysis in durum wheat germplasm for terminal drought stress - G M, VIJETH; UDAY, GOVINDAREDDY; KRISHNAPPA, GOPALAREDDY; N, SHASHIDHAR (The Indian Journal of Agricultural Sciences, 2025)
Durum wheat (Triticum durum Desf.) is an important species in wheat where drought poses a significant challenge for its productivity and world food security. The study was carried out during winter (rabi) season 2021–22 and 2022–23 at University of Agricultural Sciences, Dharwad, Karnataka to investigate the genetic variability and association between morphological and drought-responsive traits for grain yield in durum wheat collected from International Center for Agricultural Research in the Dry Areas (ICARDA) and International Maize and Wheat Improvement Center (CIMMYT). Pooled analysis of variance revealed highly significant differences (P<0.05) in the quantitative traits suggesting the indeed variability among the germplasm lines and their response to selection. Under moisture stress conditions, the genotypes exhibited high variability for traits like tillers/m, flag leaf area, peduncle length, number of grains/spike and grain yield. These traits exhibiting high genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) under both stress and non-stress condition indicates ample scope for improvement in the traits, when selection is practiced. Increase in grain yield under moisture stress was observed to be positively correlated with various factors, including the number of tillers/m, flag leaf area, peduncle length, plant height, and the number of grains/spike. Principal component analysis (PCA) explained under PC1 and PC2 showed insight for selecting traits and genotypes to improve grain yield under moisture stress where, the direct selection is ineffective. In this analysis, a total of 11 distinct components were identified, with the first four accounting for approximately 60 per cent of the variation under moisture stress conditions. The first two components exhibited strong associations with phenological, agronomic and yield-related characteristics. Germplasm lines were classified based on stress tolerance index. Tolerant (77) with STI value > 0.9, moderately tolerant (18) with STI value 0.8–0.9, and susceptible (130) with STI value < 0.8 based on their sensitivity to drought stress. In the tolerant category, the genotypes GDP2022-246, GDP2022-198, GDP2022-52, GDP2022-216, and GDP2022-47 demonstrated promising performance with good grain yield under moisture stress conditions.